Evidence Based Dentistry - Malik, Dr.Poonam; Rathee, Dr. Manu (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
It has been fascinating to observe the discussions that have playedout regarding evidence based dentistry. At one end of spectrum, some writers’portray evidence-based care as revolutionary new approaches to dental care thatwill save our profession. Other describe it time consuming process. Throughthis review describes the basis behind the use of evidence based dentistry